Regulation of myogenic activation of p38 MAPK by TACE-mediated TNFα release - Li, Yi-Ping; Niu, Airu; Wen, Yefei (Frontiers in Cell and Developmental Biology, 2014)
The activation of p38 MAPK in myogenic precursor cells is a key signal for their exit of cell cycle and entry of the myogenic differentiation program. Therefore, identification of the signaling mechanism that activates p38 MAPK during this process is important for the understanding of the regulatory mechanism of muscle regeneration. This article reviews recent findings regarding the role of inflammatory cytokine tumor necrosis factor-α (TNFα) as a key activator of p38 MAPK during myogenesis in an autocrine/paracrine fashion, and the signaling mechanisms that converge upon TNFα converting enzyme (TACE) to release TNFα from differentiating myogenic precursor cells in response to diverse regenerative stimuli.